The Importance of Using Alkaline Ionomer Binders for Screening Electrocatalysts in Alkaline Electrolyte. Issue 14 (21st November 2017) - Jervis, Rhodri; Mansor, Noramalina; Sobrido, Ana Jorge; Jones, Simon; Gibbs, Christopher; Neville, Tobias P.; Millichamp, Jason; Shearing, Paul R.; Brett, Daniel J. L.
Abstract : Many electrochemical studies exist using the acidic ionomer Nafion as a binder in the ink formulation when operating in high pH systems. However, Nafion acts as an ionic insulator for OH −, and for reactions such as the hydrogen oxidation reaction, the transport of OH − to the catalyst surface is of utmost importance when elucidating the performance of a catalyst. This work demonstrates that when using an alkaline polymer binder in the ink, the apparent activity of a commercially synthesized Pt/C catalyst is increased due to a lower diffusion resistance for the reaction. In order to obtain accurate values for kinetic data in alkaline media, the use of the acidic binder should be avoided.